2010
DOI: 10.1093/ndt/gfp728
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and significance of abdominal aortic calcification in chronic kidney disease

Abstract: Decreased GFR may be associated with the presence and extent of abdominal aortic calcification, and a high level of calcification may be associated with de novo cardiovascular events in pre-dialysis CKD, suggesting that elucidation of the mechanism through which CKD contributes to vascular calcification may lead to an improved prognosis in patients with pre-dialysis CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 38 publications
5
41
0
2
Order By: Relevance
“…Hong et al (29) postulated that the high prevalence of aortic calcification and its association with age may limit its prognostic value for the survival of patients on dialysis. The same reasoning could be applied to patients with nondialysis CKD, in whom the presence of aortic calcification is age related and very prevalent, which was reported in this study and others (1)(2)(3)(4)(5)(6)(7)(8)(9). This discovery of the independent prognostic value that a plain radiograph of hands may have in detecting VC constitutes the most original finding of this study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Hong et al (29) postulated that the high prevalence of aortic calcification and its association with age may limit its prognostic value for the survival of patients on dialysis. The same reasoning could be applied to patients with nondialysis CKD, in whom the presence of aortic calcification is age related and very prevalent, which was reported in this study and others (1)(2)(3)(4)(5)(6)(7)(8)(9). This discovery of the independent prognostic value that a plain radiograph of hands may have in detecting VC constitutes the most original finding of this study.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have reported on the high prevalence of vascular calcification (VC) in patients with nondialysis CKD (1)(2)(3)(4)(5)(6)(7)(8)(9). It has been postulated that the early diagnosis of VC and the treatment of the factors that promote it could reduce the high rate of cardiovascular mortality observed in patients with CKD (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…59,60 In brief, ten CT slices were obtained at 1-cm intervals above the bifurcation of the common iliac vessels, the cross-section of the abdominal aorta on each slice was divided into 12 sectors, and the number of calcified sectors was counted. Then, the ACI was obtained with the following formula: ACI (%) = (number of sectors with calcification)/120 (number of sectors evaluated) 3100.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Vascular calcification has been shown to be a marker of atherosclerotic plaque burden and a contributor to arterial stiffness [5]. The presence of abdominal aortic calcification (AAC) has been associated with adverse cardiovascular events, chronic kidney disease, and end-stage renal disease [6]. However, the impact of donor AAC on living kidney transplantation has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%